Integrating DT Sonic and RMS Velocity As Dual Indicators for Overpressure and Fluid Screening in The Lower Seurula Formation of The Rayeu Field, North Sumatra Basin - Pramuditya Dwi Permana; Dasapta Erwin Irawan; Agus Mochamad Ramdhan (Testing Center for Oil and Gas LEMIGAS, 2026)
Velocity anomalies are widely used as indicators of Overpressure and hydrocarbon presence in clastic sedimentary basins. However, seismic and sonic velocity responses are inherently non-unique because similar anomalies may result from unloading Overpressure, lithological variation, or fluid-related effects. This ambiguity becomes significant within the Lower Seurula Formation of the Rayeu field, North Sumatra Basin, where several wells exhibit varying production performance despite comparable velocity responses.This study proposes an integrated interpretation framework combining residual DT sonic (∆DT) and residual RMS velocity (∆VRMS) as dual indicators for Overpressure and fluid screening. The workflow integrates well log analysis, seismic-derived RMS velocity, interval velocity evaluation, clay transformation interpretation, and Fluid Replacement Modeling (FRM).Results indicate that the Lower Seurula Formation is dominated by unloading-related Overpressure, supported by persistent DT sonic deviation, interval velocity reversal, and evidence of smectite-illite transformation. FRM analysis demonstrates that gas saturation significantly reduces P-wave velocity and may generate responses similar to Overpressure anomalies. Wells exhibiting elevated ∆DT and strongly negative ∆VRMS responses generally correspond to better production performance.These findings demonstrate that integrating residual DT sonic and residual RMS velocity reduces interpretation ambiguity between unloading-related Overpressure and hydrocarbon-related fluid effects. The proposed workflow provides a practical approach for early-stage fluid screening and Overpressure evaluation in clastic sedimentary basins.